IMPLEMENTASI PROBLEM BASED LEARNING ( PBL ) TERHADAP MINAT BELAJAR PESERTA DIDIK KELAS V PADA MATA PELAJARAN PENDIDIKAN AGAMA ISLAM DI SDN MANARANG KABUPATEN MAROS - Hamsah Bur; Ilyas Tahir, Surani; Syarifa Raehana, Ahmad Razaq (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
This study aims to analyze the implementation of Problem Based Learning (PBL) to improve students’ learning interest in Islamic Religious Education at the fifth grade of SDN Manarang, Maros Regency. Thebackground of this research is the low level of student engagement and achievement in Islamic Religious Education, as shown by the pre-cycle results in which only 9 out of 27 students (34.37%) reached the minimum mastery criteria (KKM), while 18 students (65.63%) remained below the standard. This research employed Classroom Action Research (CAR) with the Kemmis and McTaggart design conducted in two cycles. Each cycle consisted of four stages: planning, acting, observing, and reflecting. Data were collectedthrough observation, tests, and interviews, and were analyzed descriptively both quantitatively and qualitatively. The results showed that students’ learning interest and achievement improved significantlythrough the application of PBL. The average score increased from 51.85% in the pre-cycle with 22.22% mastery, to 67.77% in cycle I with 44.44% mastery, and to 84.07% in cycle II with 100% mastery. In addition, the distribution of students’ learning interest shifted from the categories of very poor and poor in the pre-cycle to the categories of good and very good in cycleIt can be concluded that the use of PBL in Islamic Religious Education is effective in improving bothstudents’ learning interest and achievement. The findings suggest that PBL can serve as an alternative model to enhance the quality of Islamic Religious Education in elementary schools.